Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.

Multifaceted core-shell nanoparticles: superparamagnetism and biocompatibility - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Ahir, Manisha; Adhikary, Arghya; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2015)
NicoreAgshell nanoparticles were synthesized by redox transmetallation reaction. Reduction potential match was encouraging to attempt the synthesis of the NicoreAushell system too. However, it could be achieved only after an effective surface modification on the Ni-core. Thorough characterization (UV-Vis spectroscopy, fluorescence spectroscopy, XRD, XPS, FTIR, TEM, and EDX) proved the necessity of surface modification and the success of synthesis of both types of core-shell structures. The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirmed the surface modification of Ni nanoparticles and the interactions involved between the ligands and metals (in the core and/or the shell) at various steps of the synthetic process. Even after the formation of the noble metal shell, the magnetic core was found to retain its superparamagnetic nature. In addition, the Au-shell protected the core from aerial oxidation and decreased toxicity as compared to pristine Ni nanoparticles as observed by MTT assay on normal cells (PBMCs).

Facile synthesis of ZnO-Ag nanocomposite and its photocatalytic activity - Sardar, Debasmita; Maity, Jayeta; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
The evolution of photoactive hybrid materials (e.g. noble metal-semiconductor) has resulted in heterogeneous photocatalysis. We report a facile route for the synthesis of ZnO-Ag nanocomposites with varying percentage of loading of the noble metal, expecting a great boost in the photocatalytic behavior of ZnO. The as prepared material was thoroughly characterized by UV-Vis, FTIR, TEM, FESEM, XRD, XPS analyses. The photocatalytic activities of the nanocomposites have been assessed from the ability to degrade methylene blue dye in aqueous solution. The results suggest that incorporation of Ag nanoparticles on the surface of ZnO particles can enhance catalytic activity in comparison to pure ZnO particles under visible light by minimizing the recombination of photogenerated electron-hole pairs.

Multiple functionalities of Ni nanoparticles embedded in carboxymethyl guar gum polymer: catalytic activity and superparamagnetism - Sardar, Debasmita; Sengupta, Manideepa; Bordoloi, Ankur; Ahmed, Md. A.; Neogi, S. K.; Bandyopadhyay, Sanjoy; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (Applied Surface Science, 2017)
Composites comprising of metallic nanoparticles in polymer matrices have allured significant importance due to multifunctionalities. Here a simple protocol has been described to embed Ni nanoparticles in carboxymethyl guar gum (CMGG) polymer. The composite formation helps in the stabilization of Ni nanoparticles which are otherwise prone towards aerial oxidation. Further the nanoparticles retain their superparamagnetic nature and catalytic capacity. Ni-Polymer composite catalyses the reduction of 4-Nitrophenol to 4-Aminophenol very efficiently in presence of NaBH4, attaining a complete conversion under some experimental conditions. Ni-Polymer composite is well characterized using UV–vis spectroscopy, FTIR, XPS, powder XRD, TGA, SEM and TEM. A detailed magnetic measurement using superconducting quantum interference device-vibrating sample magnetometer (SQUID-VSM) reveals superparamagnetic behaviour of the composite.

Organic phase transmetallation approach for synthesis of hollow Ni-Au nanocomposites with tunable cavity size - Sardar, Debasmita; Ahmed, Md Azaharuddin; Bandyopadhyay, Sudipta; Ghosalya, Manoj Kumar; Bala, Tanushree (New Journal Of Chemistry, 2018)
Ni-Au nanocomposites in the form of hollow spheres with controlled cavity size have been successfully synthesized by the transmetallation reaction between hydrophobized Ni nanoparticles and hydrophobized Au precursors. This can be considered as a fairly unique synthesis strategy that does not require any additional external reductants. The synthesis is carried out in a nonpolar solvent and precise tuning of the cavity size has been achieved only by varying the ratio of the two reacting components. A detailed characterization has been performed via UV-vis spectroscopy, XPS, TEM, EDAX, and SEM. The mechanistic aspect is established from FTIR. SQUID-VSM confirmed the magnificent superparamagnetism of the nanocomposites.

Dexterous route for synthesis of hollow spherical ZnO and ZnO-Ag nanocomposite with superior photocatalytic ability - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree (ChemistrySelect, 2019)
Hollow spherical ZnO and hollow ZnO-Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO-Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV-Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity.
Keywords: excellent photocatalysis; synthesis; template free; ZnO hollow nanoparticles; ZnO-Ag nanocomposite